3.4k views
3 votes
The value of x in this system of equations is 1.

3x + y = 9

y = –4x + 10

Substitute the value of y in the first equation:
Combine like terms:
Apply the subtraction property of equality:
Apply the division property of equality:
3x + (–4x + 10) = 9

–x + 10 = 9

–x = –1

x = 1

What is the value of y?

User Weiling
by
5.5k points

2 Answers

5 votes

Answer:

In my opinion the answer is y = 6

Explanation:

We have two unknowns from the equation therefore, two equations are needed. These equations are:

3x + y = 9

y = –4x +10

To solve for y, we first substitute the second equation to the first one.

3x + –4x +10= 9

x = 1

We substitute the value of x to either of the equations and solve for y.

y = –4(1) +10

y = 6

3 votes

Answer:

y=6

Explanation:


3x + y = 9


y = -4x + 10

Substitute the value of y in the first equation:


3x + (-4x + 10) = 9

Apply the subtraction property of equality:


-x + 10 = 9


-x=-1

x=1

Substitute 1 for x in the given y equation


y = -4x + 10


y = -4(1)+ 10

y=6

User Artem Klevtsov
by
5.8k points